Rural Agribusiness-Based Agropolitan Area Development and Environmental Management Sustainability: Regional Economic Growth Perspectives - Surya, Batara; Saleh, Haeruddin; Hamsina, Hamsina; Idris, Muhammad; Ahmad, Despry Nur Annisa (International Journal of Energy Economics and Policy, 2020)
Regional development in developing countries is predominantly oriented towards exploitation of natural resources and tends to ignore environmental problems. Optimization of the utilization of natural resources towards the development of the agropolitan area has an impact on economic growth and increases farmers’ income in rural areas. This study aims to examine the significance of the development of agropolitan-based agribusiness areas in rural areas and the direct and indirect relationship of the development of agropolitan-based agropolitan areas to the improvement of community productive economic endeavors and ecosystem sustainability. Research data were obtained through observation, surveys, and documentation. The research method used a qualitative-quantitative combination in sequence. The results of the regression analysis show that the development of the agropolitan area has a significant effect on regional economic growth, and the results of the path analysis confirm that the development of the agropolitan area based on rural agribusiness has a significant effect on increasing the productive economy of the community and the ecosystem sustainability. The results of this study confirm that an increase in the productivity of the regional economic base sector has an impact on the development of agropolitan areas based on the rural agribusiness system in the direction of increasing community income and the regional economy. This article offers the concept of system integration in the development of agropolitan areas based on ecosystem sustainability and regional economic growth in developing countries. Keywords: Agropolitan Area; Economic Growth; Rural Agrobusiness; Economic Effort; Ecosystem Sustainability JEL Classification: Q5 DOI: https://doi.org/10.32479/ijeep.10184